Bifurcated dissociative photoionization mechanism of acetic acid anhydride revealed by imaging photoelectron photoion coincidence spectroscopy. Issue 36 (26th August 2016) - Voronova, Krisztina; Mozaffari Easter, Chrissa M.; Torma, Krisztián G.; Bodi, Andras; Hemberger, Patrick; Sztáray, Bálint
Abstract : PEPICO allows us a peek beyond the transition state to identify bifurcated reaction pathways. Abstract : The fragmentation processes of internal energy selected acetic acid anhydride cations, Ac2 O +, were investigated by imaging photoelectron photoion coincidence (iPEPICO) spectroscopy. The first dissociation channel leads to the formation of CH3 C(O)OCO + ( m / z = 87) by a CH3 -loss. The 0 K appearance energy ( E 0 ) was determined to be 10.289 ± 0.010 eV, in excellent agreement with the G4-calculated 10.28 eV transition state (TS) energy. Based on the thermochemical onset of CH3 C(O)OCO +, a reverse barrier of 40 kJ mol −1 was found. The second dissociation channel leads to the formation of the acetyl cation, CH3 CO + ( m / z = 43). The appearance of trace amounts of acetone in the mass spectra, statistical modeling of the branching ratios, and quantum chemical calculations point to the existence of a post-transition-state bifurcation on the potential energy surface and a single TS leading to multiple products. That is, at higher excess energies, the CH3 -group may swerve back along an orbiting pathway to form the acetone cation by CO2 -loss instead of leaving directly. The acetone cation thus formed is then energetic enough to lose a methyl group and yield the acetyl cation at a phenomenological E 0 = 10.316 ± 0.015 eV. The acetyl cation, which dominates the breakdown diagram up to 16 eV photon energy, is also formed by sequential CO2 -loss from the CH3 C(O)OCO + intermediate at E 0 = 10.53 ± 0.03 eV. The CH3 + ( m / z = 15) fragment ion appears above 13 eV photon energy. This species can be produced directly from the parent ion or via two sequential dissociation channels: by acetyl radical loss from the acetone cation or CO-loss from the acetyl cation.